Pengaruh NPM, ROA, ROE terhadap Harga Saham pada Perusahaan LQ45 - Sahari, Kannia Aulia; Suartana, I Wayan (E-Jurnal Akuntansi, 2020)
The purpose of this study is to determine the movement of stock prices, namely fundamental analysis where profitability ratios are often used in fundamental analysis, namely NPM, ROA and ROE This research was conducted on companies incorporated in the 2014-2018 LQ45 index on the Indonesia Stock Exchange. The research population is 68 companies. Samples were selected using a purposive sampling technique so that the number of samples obtained was 26 companies and the number of observations over 5 years was 130 observations. Data analysis techniques using multiple linear regression analysis. Based on the results of this analysis show that NPM and ROA have no effect on stock prices so that they are unable to increase share prices in companies incorporated in the LQ45 index, while ROE affects stock prices so the higher the ROE level the higher the stock prices at companies incorporated in the LQ45 index. Keywords: NPM; ROA; ROE; Stock Price.